Structural properties and antioxidant activities of polysaccharides isolated from sunflower meal after oil extraction - Hua-Min Liu (Elsevier, 2021)
Making full use of sunflower seeds, including oil and the polysaccharides extracted from the meals which oil has been extracted, is one way to enhance their industrial value. Such meals contain abundant polysaccharides; however, the application of polysaccharides isolated from sunflower remaining meals after oil extraction has not been investigated. In this study, polysaccharides were isolated by alkali from sunflower meals after different oil extraction processes, and their structural properties and antioxidant activities were compared. The results indicated that these polysaccharides displayed significant variability in monosaccharide composition and molecular weight. Differences in structural properties could result in differences in functional antioxidant properties. The polysaccharide (SPHE-1) obtained from the meals after traditional hexane extraction exhibited the best antioxidant activities, including DPPH free radical-scavenging assay and hydroxyl radical scavenging activity among all the polysaccharide fractions. The research provides valuable information for making efficient use of sunflower seeds in the food industry.